2020
DOI: 10.1097/md.0000000000019092
|View full text |Cite
|
Sign up to set email alerts
|

Ecological study on needs and cost of treatment for dental caries in schoolchildren aged 6, 12, and 15 years

Abstract: To determine the treatment needs and the care index for dental caries in the primary dentition and permanent dentition of schoolchildren and to quantify the cost of care that would represent the treatment of dental caries in Mexico. A secondary analysis of data from the First National Caries Survey was conducted, which was a cross-sectional study conducted in the 32 states of Mexico. Based on dmft (average number of decayed, extracted, and filled teeth in the primary dentition) and DMFT (average nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…The caries levels appear to be similar to studies previously conducted in Mexico and other countries. For example, another study from Mexico focused on a general child population of a similar age reported a greater experience and prevalence of dental caries in primary than permanent dentition [ 6 ], with a range of the dmft index between 0.73 and 5.35 at 6 years of age, and DMFT index between 0.52 and 3.67 at 12 years of age. Other reports have suggested that the caries prevalence in permanent dentition ranges from 70% to 85% among 12-year-old children [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The caries levels appear to be similar to studies previously conducted in Mexico and other countries. For example, another study from Mexico focused on a general child population of a similar age reported a greater experience and prevalence of dental caries in primary than permanent dentition [ 6 ], with a range of the dmft index between 0.73 and 5.35 at 6 years of age, and DMFT index between 0.52 and 3.67 at 12 years of age. Other reports have suggested that the caries prevalence in permanent dentition ranges from 70% to 85% among 12-year-old children [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dental caries has both a high prevalence and incidence, mainly in those with a socioeconomic disadvantage, and continues to be a serious global health problem [ 2 ]. In Latin America [ 3 , 4 , 5 ] and Mexico, school-age children and adolescents have considerable treatment needs and low experiences of dental services for restorative and preventive treatment [ 6 , 7 ]. Caries impacts diverse aspects of life; for example, dental caries may be associated with dental pain, failure to thrive, and negative effects on body weight and height, and may affect one’s quality of life [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…While in Latin America there is only a small number of countries that report dental health status with nationally representative samples [2], dental caries is the most prevalent oral disease [3]. In Mexico, the situation is similar, with low utilization of preventive dental services and high prevalence of caries and treatment needs in children and adolescents [4][5][6][7][8][9][10]. In general, about half of individuals between 6 and 12 years of age present caries lesions in any tooth of either primary or permanent dentition [4,10], with consequences in terms of pain, suffering, functional impairment, and reduced quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…En México, a los 6 años, la caries dental en la dentición primaria alcanza valores, de los índices de ceod, que van de 0.73 a 5.35 y prevalencias (18) entre el 26.3% a 77.5% . Por lo que también en México se trata del principal problema de salud pública bucal, ya que tiene diversos impactos en las (19)(20)(21)(22) personas, familias y el sistema de salud .…”
Section: Proceso De Desmineralización-remineralización Del Esmalte Deunclassified